Commercial electricity demand modeling: Do regional differences matter for Saudi Arabia? - Jeyhun I. Mikayilov; Abdulelah Darandary (Energy Reports, 2023)
This paper estimates the responses of drivers of electricity demand for commercial consumers in Saudi Arabia at a regional level. We demonstrate that the regional variation of response to changes in income and prices reflects the level of development of the commercial sector per region. The Southern region’s commercial electricity demand is sensitive to income, a 1% increase in income levels generates a ∼3% increase in demand for electricity, and the income elasticity is lowest for the Eastern region, 0.5%. Compared with residential and industrial consumers, electricity prices for the commercial sector play a significantly more prominent role in driving demand in all regions except the Eastern one. For a 10% increase in commercial electricity price, we estimate that demand will decrease by 12.5% in the Western region, 6% in the Southern region, and 8% in the Central region. In comparison, the price elasticity is much less impactful for the Eastern region, with a decrease of 1.8% for a 10% price increase. The paper makes region-specific policy suggestions based on the diverse income and price responses to the electricity demand of commercial consumers across regions.